The impact of financial development on economic growth in Iraq for the period (2004-2018):An Analytical Econometric Study - Faraj, Mardin Mahsum (Journal of Economics and Administrative Sciences, 2021)
The objective of this study is to measure the impact of financial development on economic growth in Iraq over the period (2004-2018) by applying a fully corrected square model (FMOLS) Whereas, a set of variables represented by (credit-to-private ratio of GDP, the ratio of money supply in the broad sense of GDP, percentage of bank deposits from GDP) were chosen as indicators for measuring financial development and GDP to measure economic growth. Major tests have been carried out, such as the stability test (Unite Root Test), the integration test (Cointegration). Results of the study showed that there is a clear and positive relationship between (credit-to - GDP ratio of the private sector, bank-to-GDP ratio) and economic growth on the one side, and the presence of a negative relationship between (the ratio of the money supply to GDP in the general sense) and economic growth in Iraq, The study concluded with a set of recommendations, including the need for Iraq’s Central Bank to review credit facility supervisory tools with a view to liberating commercial banks from all financial compliance policies, which would encourage them to increase the volume of bank loans to the private sector with a view to advancing Iraqi economic activity